2019
DOI: 10.1093/alcalc/agz033
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Personal Alcohol Consumption on Aspects of Medical Student Alcohol-Related Competencies

Abstract: Health professionals need to be competent to assess the level of alcohol use in patients. In this study, we aimed to explore how medical students' own alcohol consumption has an impact on their familiarity with alcohol brands, strengths and alcohol related harms. Methods As part of an investigation the concept of 'alcohol health literacy', this study combined an anonymous online survey, linked to an electronic alcohol 'brand' recognition game. Participants were medical students in their first clinical year. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…At preparation phase, we used the “estimating an infinite population mean” formula to calculate the sample size. The standard deviation of response time of 2.5 s from Sinclair et al [ 30 ] and a margin of error of 0.2 s were used to determine the target sample size, which was 601 participants for this study. An estimate of 30% of unusable data from a sample of 601 participants was considered.…”
Section: Methodsmentioning
confidence: 99%
“…At preparation phase, we used the “estimating an infinite population mean” formula to calculate the sample size. The standard deviation of response time of 2.5 s from Sinclair et al [ 30 ] and a margin of error of 0.2 s were used to determine the target sample size, which was 601 participants for this study. An estimate of 30% of unusable data from a sample of 601 participants was considered.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study of women presenting to breast health services concerned about breast cancer, we found that there was often what we termed a ‘collusion of denial’. This was where staff stated that they assumed that if patients were concerned or wished to talk about alcohol they would raise the topic, whereas patients assumed that if alcohol was a relevant factor in the management of their health then staff (surely) would be asking about it (Sinclair 2019b).…”
Section: Alcohol-related Health Literacy Among Cliniciansmentioning
confidence: 99%